2014
DOI: 10.1111/pbi.12185
|View full text |Cite
|
Sign up to set email alerts
|

Plant‐derived recombinant immune complexes as self‐adjuvanting TB immunogens for mucosal boosting of BCG

Abstract: SummaryProgress with protein-based tuberculosis (TB) vaccines has been limited by poor availability of adjuvants suitable for human application. Here, we developed and tested a novel approach to molecular engineering of adjuvanticity that circumvents the need for exogenous adjuvants. Thus, we generated and expressed in transgenic tobacco plants the recombinant immune complexes (RICs) incorporating the early secreted Ag85B and the latency-associated Acr antigen of Mycobacterium tuberculosis, genetically fused a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(28 citation statements)
references
References 52 publications
(59 reference statements)
0
28
0
Order By: Relevance
“…Plant-expressed RIC were first shown to be immunogenic and protective against C. tetani challenge [20]. More recently, we reported that Ebola RIC could induce protective antibodies against the Ebola virus [1,21], while similar studies performed elsewhere showed that tuberculosis-based RIC (TB-RIC) [22] confer statistically significant protection against M. tuberculosis infection. Others have shown that immune complexes can substantially enhance antibody responses to HIV gp120 [17][18][19].…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Plant-expressed RIC were first shown to be immunogenic and protective against C. tetani challenge [20]. More recently, we reported that Ebola RIC could induce protective antibodies against the Ebola virus [1,21], while similar studies performed elsewhere showed that tuberculosis-based RIC (TB-RIC) [22] confer statistically significant protection against M. tuberculosis infection. Others have shown that immune complexes can substantially enhance antibody responses to HIV gp120 [17][18][19].…”
Section: Discussionmentioning
confidence: 85%
“…Studies by Hioe and coworkers indicate that immune complexes substantially enhanced antibody responses against HIV gp120 [17][18][19]. We and others have explored the possibility of designing immune complex vaccines against a number of pathogens including Clostridium tetani [20], Ebola virus [1,21] and Mycobacterium tuberculosis [22]. This approach is based on generating recombinant immune complexes (RIC) using a monoclonal antibody specific for a particular antigen and expressed in fusion with that antigen (at the C-terminus of the heavy chain).…”
Section: Introductionmentioning
confidence: 99%
“…IFN-g was also activated when either Ag85B or Acr stimulus was present. Remarkably, in terms of immunoprotection, BCG-immunized mice boosted with TB-RICs showed a significant reduction on lung M. tuberculosis infection, at lower levels than the observed in the group immunized only with BCG [68]. The successful use of immune complexes based on antibody chains was previously proven in plant systems by targeting an HIV antigen and thus this technology is considered a convenient configuration leading to high immunogenicity [69,70].…”
Section: Immune Complexes Based On Ag85b and Acr Antigensmentioning
confidence: 99%
“…Using similar approaches, multiple antigens have been expressed in tobacco being able to induce both humoral and cellular immune responses that protected against intracellular pathogens such as Mycobacterium tuberculosis. Intranasal immunization of mice with ICs boosted the Bacillus Calmette-Guerin strain vaccine (BCG)-induced immunity and, importantly, conferred further protection against M. tuberculosis infection [92]. Remarkably, these methodologies have been applied to target viruses.…”
Section: Immune Complexesmentioning
confidence: 99%